Insurance, fire and the peri-urban: perceptions of changing communities in Melbourne's rural-urban interface. Issue 1 (2nd January 2022) - Young, Travis; Lucas, Chloe; Booth, Kate
ABSTRACT: Across the world, cities are growing, blurring lines between urban and rural. In Australia, peri-urban areas are undergoing demographic shifts and extensive development. In the literature, these shifts are characterised by differences in the risk perceptions and hazard experiences between established and incoming residents. In this paper, we illustrate how some of these differences are perceived by focusing on house and contents insurance in the bushfire-prone City of Whittlesea on the fringes of Greater Melbourne. This location captures the complex relationship between growing population and high bushfire risk, and is the site of the country's deadliest bushfire event, Black Saturday, in 2009. Through in-depth interviews, we observe that residents perceive insurance as playing a role in peri-urban change. Specifically, underinsurance is understood to be a challenge faced by many impacted by the Black Saturday fires, and contributes to feelings of uncertainty regarding the capacities of changing communities to work together to prepare for and recover from future fires. Our focus on insurance is informed by the need to better understand the social qualities of this dimension of disaster preparedness and recovery, and how perceptions of insurance amid peri-urban change may help produce social patterns and trends.